PENGARUH EDUKASI DIGITAL TERHADAP PENGETAHUAN DAN SIKAP DETEKSI DINI KANKER PAYUDARA PADA PASIEN PEREMPUAN DEWASA DI POLIKLINIK PENYAKIT DALAM DI RS GRHA KEDOYA JAKARTA BARAT - Mistiani Puspitasari; Juliastuti, Dyah; Dewi Anggraini (Jurnal Kesehatan STIKes IMC Bintaro, 2024)
Cancer is one of the most feared diseases and is seen as the main cause of death throughoutthe world. This disease, which can cause death, is still a threat to human welfare and healthin general. Research Objective: To determine the effect of digital education on knowledgeand attitudes towards early detection of breast cancer in adult female patients at the generalpolyclinic at Grha Kedoya Hospital, West Jakarta. Research Method: This study used a preexperimental design type one group pretest-posttest and respondents were recruited usingQuota Sampling. The analysis technique uses the T-test. Research Results: The averagevalue of knowledge about early detection of breast cancer before and after digital educationwas (66.25%) and (82.19%) Meanwhile, the average value of attitude regarding earlydetection of breast cancer before and after digital education was 13 respondents (40.6%)and 27 respondents (84.4%) Conclusion: there is an influence of digital education onknowledge and attitudes towards early detection of breast cancer in adult female patients inthe general polyclinic at Grha Kedoya Hospital, West Jakarta in 2023 (P-value 0.000 and0.000). Suggestion: It is hoped that nurses can utilize digital education methods to increasewomen's knowledge and attitudes towards early detection of breast cancer as part ofprofessional nursing care for outpatients and Indonesian women in general.